BIAS GENDER DALAM PENGGUNAAN MEDIA PEMBELAJARAN BUKU REFERENSI BAHASA INGGRIS SMA KELAS II “INFORMATIONAL ENGLISH” - Nur - Hidayanto (Universitas Negeri Yogyakarta, 2007)
Abstract Gender issues become hot phenomena today. The demand for equality in education, economy, politics, social and culture is so strong that it tries to stop gender issues rush. It occurs when women feel that there is unfairness between women and men rights. The unfairness is in the form of subordination, marginalization, inequality in responsibility and also women stereotype. The writer tries to find out the gender issues in the English Reference Book for 2nd year students of Senior High School entitled Informational English written by Bambang Kiswanto and Tony Rogers and published by Widya Utama in 2005. He investigates the use of language and also pictures which shows gender issues. Then, he compares it with theories and also facts in the real world. The writer finds that there are some gender issues in the book. They are in the form of inequality in the percentage of women and men pictures, the use of English pronouns, professions, emotion expressed in texts, famous persons, artists and also characterizations. In conclusion, the book illustrates some gender issues which often occur in the real life.